Management of Broodstock for Pacific White Shrimp (Litopenaeus vannamei) at the Center for Superior Shrimp and Shellfish Broodstock Production (BPIU2K) Karangasem, Bali - Maolana, Arman; Muahiddah, Nuri (Journal of Fish Health, 2024)
Shrimp (Litopenaeus vannamei), as it directly impacts the quality and quantity of larvae produced for aquaculture. This study investigates the management practices at the Center for Superior Shrimp and Shellfish Broodstock Production (BPIU2K) in Karangasem, Bali, focusing on the broodstock selection, breeding, and maintenance processes. The research evaluates the performance of broodstock in terms of growth, reproductive health, and overall productivity, aiming to optimize practices for sustainable shrimp farming. Data was collected through direct observation, water quality analysis, and broodstock health assessments. The findings highlight the importance of proper environmental conditions, nutritional management, and genetic selection in enhancing the reproductive success of L. vannamei. The study also discusses challenges faced by the facility, including disease management and genetic diversity, offering recommendations for improving broodstock management to ensure consistent, high-quality shrimp production. The number of male broodstock in the maintenance tank was around 250, and female broodstock was around 200, with a survival rate of 70%. This research contributes to advancing sustainable aquaculture practices and improving the shrimp farming industry in Indonesia.